Changes in the juvenile fish assemblage of a Mediterranean shallow Posidonia oceanica seagrass nursery area after half century - DÍAZ-GIL, CARLOS; GRAU, AMALIA; GRAU, ANTONIO MARIA; PALMER, MIQUEL; CABRERA, REMEDIOS; JORDÀ, GABRIEL; CATALÁN, IGNACIO ALBERTO (Mediterranean Marine Science, 2019)
The within-year dynamics of the juvenile fish community over a shallow nursery seagrass-dominated habitat (Posidonia oceanica) in a Mediterranean Bay was compared between two surveys separated 50 years (1960 and 2012-2013). A nocturnal survey over depths ranging from 2 to 10 m over patched seagrass meadows was conducted for one year (2012-2013) through 72 epibenthic tows spread fortnightly in 4 close-by stations, mimicking a survey, conducted in 1960, in terms of sampling intensity, sampling zone, temporal coverage and sampling gear. Although a large proportion of fish species was similar among surveys, remarkable and statistically significant differences were detected. A striking feature was that one of the most common and abundant sparidae species nowadays, Diplodus annularis, did not appear in 1960. Other strong differences included the disappearance of European eel Anguilla anguilla in the recent survey. Further, one of the most valuable species for artisanal fisheries in the area, the black scorpionfish Scorpaena porcus, was almost 10 times less abundant in 1960. A finer-scale study of the 2012-2013 survey allowed a quantitative analysis between species composition and potential environmental drivers through Redundancy Analysis that described well the current pattern of time-dependent recruitment pulses in nearshore meadows from the area through a year, with marked effects of surface temperature and photoperiod. The comparison between surveys suggests that some strong differences between surveys are unlikely attributable to interannual stochasticity in recruitment or environmental variability but may be related with i) unaccounted for habitat transformation and/or ii) the strong decrease of juvenile fishing mortality in this shallow nursery area since the enforcement of bans on littoral epibenthic trawling activities characteristic of this area.